Developing assessment instruments: The effect of a reviser’s profile on the quality of the revision product - van Rensburg, Alta (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2018)
Translation revision is such a new field of study that there are still very few empirical studies from which to learn more about matters such as the ideal profile of a reviser or the assessment instruments with which to determine the quality of a revision product. This article describes the development of two such assessment instruments. Instrument 1 employs categories that describe a revision product and Instrument 2 comprises a formula for quantifying the quality of a revision product. These assessment instruments were applied in an empirical study involving 30 revised translations to determine whether there is any relationship between aspects of a reviser’s profile, such as qualifications and translation and revision experience, and the quality of their revision product.